Digital-Based Strategies for Improving Land and Building Tax Service Quality at the Regional Revenue Agency of Palu City - Ade Irma; Mustainah M; Irwan Waris; Nasrullah (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
This study show of the devolution of Land and Building Tax (PBB-P2) administration to Indonesian local governments under fiscal decentralization legislation fundamentally repositions subnational authorities as autonomous fiscal actors; however, persistent revenue shortfalls in post-disaster urban settings reveal structural governance deficits that remain theoretically underexamined. Employs a descriptive qualitative approach grounded in interpretivist governance research, drawing on semi-structured interviews with senior Bapenda Palu City officials, PAD realization records covering 2022–2025, and regulatory documentation. Data were analyzed using Miles, Huberman, and Saldana's interactive model and triangulated across interview, observational, and documentary sources. Findings – reveal that while Bapenda Palu has invested substantially in digital infrastructure encompassing the SIPABETA platform, multi-channel payment systems, and mobile sub-district outreach structural governance deficiencies persist: PBB-P2 revenue realization systematically underperformed targets by between 26.5% and 34.35% across 2023–2025, approximately 8,632 tax object records remain data-deficient due to GPS inaccuracies and incomplete address data, and elderly (lansia) taxpayers are excluded from digital service channels. Originality – carry practical implications for fiscal decentralization policy design across post-disaster subnational governments throughout Indonesia.